Hybridity in early modern art - Elston, Ashley (Ashley Jane); Rislow, Madeline (New York, NY : Routledge, 2022)
"This collection of essays explores hybridity in early modern art through two primary lenses: hybrid media and hybrid time. The varied approaches in the volume to theories of hybridity reflect the increased presence in art historical scholarship of interdisciplinary frameworks that extend art historical inquiry beyond the single time or material. The essays engage with what happens when an object is considered beyond the point of origin or as a legend of information, the implications of the juxtaposition of disparate media, how the meaning of an object alters over time, and what the conspicuous use of out-of-date styles means for the patron, artist, and/or viewer. Essays examine both canonical and lesser-known works produced by European artists in Italy, northern Europe, and colonial Peru, ca. 1400-1600. The book will be of interest to art historians, visual culture historians, and early modern historians"--
Connecting Human and Divine: Carlo Crivelli's Hybrid Media / Amanda Hilliam -- Collaboration and Dissonance in Siena's Bichi Altarpiece / Ashley Elston -- Emblems and Hybridity in a Southern German Epitaph Sculpture / Catharine Ingersoll -- Hybridity, Media, and Source Material in Visual Representations of the Wild Woman: Transitions from Hand-Copied Manuscripts to Hand-Press Prints / Michelle Moseley-Christian -- Material Legacy: Hybridity and French Manuscript Illumination from the Late Fifteenth through Sixteenth Centuries / Larisa Grollemond -- Visual Hybridity in the Sancta Sanctorum (Rome): Reframing the Middle Ages / Kirstin Noreen -- (Re-)Encasing the Ashes of St. John the Baptist in Genoa Across Time / Madeline Rislow -- Recycling, Renaissance Style: Hybridity and Giorgio Vasari's Pieve Altarpieces / Sally J. Cornelison -- Style and Meaning Beyond Europe: Bernardo Bitti and Mannerism / Christa Irwin.
Keywords: Art, European -- Themes, motives; Cultural fusion and the arts; ART / History / Renaissance